Cross-national learning assessments: relationship to educational policy curriculum and capacity development in Kenya, Tanzania and South Africa - Mulongo, Godfrey Wanyonyi (My University, 2017)
Utilizing the theories of change and social development, this study analyzes the extent to which participation in cross-national learning assessments has influenced educational policy and curriculum reforms in three African countries: Kenya, Tanzania and South Africa. The study also interrogates structural reforms and exchange of technical capacities and evaluates the culture of learning assessment in these countries. To collect data, the researcher conducted semi-structured interviews with key informants drawn from the Ministries of Basic Education, national examinations councils, civil society organizations and curriculum development institutions in the three countries. In total, 17 key informant interviews were conducted (five in Kenya and six a piece in Tanzania and South Africa). The interviews were complemented by summative content review of policy/strategic papers. This study shows that overall, at least 18 policy/official strategic documents were formulated in these three countries (seven in Kenya and six in Tanzania and five South Africa) as a consequence of participating in the cross-national learning assessments. Five curriculum reforms attributable to the participation in the cross-national learning assessments are also recorded. However, the findings of the current study suggest that these curriculum reviews have not critically considered learning outcomes and are limited in relation to content, design, delivery mechanisms and assessment of literacy and numeracy programmes. As far as teacher capacity is concerned, the study has established that teachers in these countries lack skills in measurement mainly due to the limited training or lack of coverage on psychometrics in the teacher training curricula. Capacity to implement own national learning assessments is varied across the three countries. South Africa and to some extent Kenya have demonstrated improved capacities to implement independent large-scale learning assessments. Much progress has however been made by South Africa in resourcing and implementing independent large-scale learning assessments, an indication of commitment to sustain the culture of monitoring of learning outcomes. There is also much variation in policy and programme formulation and resource investment in literacy programmes across the three countries; at least three programmes/initiatives in South Africa and one each in Kenya and Tanzania have been launched to respond to learning challenges especially in lower grades, with at least $USD 645.2 million invested between 2010-2015. However, the programmes in Kenya and Tanzania are technically and financially donor driven. In terms of structures, South Africa and Kenya have put in place official structures that could support the sustainability of the system of monitoring learning outcomes. For sustainability, a recommendation is made that learning assessments be decentralized and collaboratively managed with stakeholders at the provincial and county/local council levels. The study concludes by discussing the social development implications of these findings.
A Research Dissertation Submitted for the Degree of Doctor of Philosophy The Department of Psychology School of Human and Community Development Faculty of Humanities University of the Witwatersrand May, 2017
Keywords: College students--Rating of.; Education, Higher--Evaluation--Cross-cultural studies; International education